If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(9h + 5) = 0 Reorder the terms: 3(5 + 9h) = 0 (5 * 3 + 9h * 3) = 0 (15 + 27h) = 0 Solving 15 + 27h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 27h = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 27h = 0 + -15 27h = 0 + -15 Combine like terms: 0 + -15 = -15 27h = -15 Divide each side by '27'. h = -0.5555555556 Simplifying h = -0.5555555556
| 2b+15=3b+7 | | 24i-18=5 | | 7x-3+y=27 | | x^2/0=1 | | (3z-5)(8-z)=0 | | y=6(3)-13 | | 4p/10=20 | | 5z(4z+3)=150 | | 4x+23=21x-1 | | x-4)(x-4)/x^2-3x-15=47 | | (x-4)(x-4)/x^2-3x-15 | | whatisx+5=10 | | 150=41+x | | 8x-4=2x | | f(x)=0.25x^4-2x^3 | | 11/x-5=3 | | 25=30y | | 4.3/1.9 | | 10/x=13 | | 2=-6x+15y | | -0.45/1.8=0.81/z | | 2e^15x=11 | | 7x-(4x+32)=12 | | (5/6)x-3=7 | | 1/x=-13 | | (18n)(5)= | | -6-1/2p=8 | | -5(4x+3)= | | 62=-7a-43 | | 2-15y=-6x | | -3/2X-1/25/2 | | -7-9y-9= |